Prevalence and Characterization of Cryptosporidium Species in Tibetan Antelope (Pantholops hodgsonii) - Qin, Si-Yuan; Sun, He-Ting; Lyu, Chuang; Zhu, Jun-Hui; Wang, Zhen-Jun; Ma, Tao; Zhao, Quan; Lan, Yun-Gang; He, Wen-Qi (Frontiers in Cellular and Infection Microbiology, 2021)
Cryptosporidium is an enteric apicomplexan parasite, which can infect multiple mammals including livestock and wildlife. Tibetan Antelope (Pantholops hodgsonii) is one of the most famous wildlife species, that belongs to the first class protected wild animals in China. However, it has not been known whether Tibetan Antelope is infected with Cryptosporidium so far. The objective of the present study was to determine the prevalence and characterization of Cryptosporidium species infection in Tibetan Antelope and the corresponding species by using molecular biological method. In the current study, a total of 627 fecal samples were randomly collected from Tibetan Antelope in the Tibet Autonomous Region (2019–2020), and were examined by PCR amplification of the small subunit ribosomal RNA (SSU rRNA) gene. Among 627 samples, 19 (3.03%, 19/627) were examined as Cryptosporidium-positive, with 7 (2.33%, 7/300) in females and 12 (3.67%, 12/327) in males. The analysis of SSU rRNA gene sequence suggested that only two Cryptosporidium species, namely, C. xiaoi and C. ubiquitum, were identified in this study. This is the first evidence for an existence of Cryptosporidium in Tibetan Antelope. These findings extend the host range for Cryptosporidium spp. and also provide important data support for prevention and control of Cryptosporidium infection in Tibetan Antelope.